Trends of digitalization process in Ukraine - Polozova, T. V.; Sheiko, I. (Pan-European Institute, 2021)
The world has entered a new era when the impact of digital technologies is increasingly felt in all sectors of the economy. Digitalization is radically changing traditional industries and sectors.
Keywords: digitalization processes; digital economy